(untitled) (ENTHYMEMA, 2016)
This paper focuses on the ‘history of medicine’ outlined by the author of the Hippocratic treatise On Ancient Medicine, in order to reflect on the relationship between medicine and narrative in Classical Greece. At the outset of the work, the author provides an account of the beginnings of his discipline, conceiving of medicine’s history as a continuum of research and findings that unravel the nature of the human body and the cause of diseases. As this paper shows, the physician-narrator assigns to his craft a crucial role in fostering the birth and progress of human civilization. The rhetorical goals of the historical account are, as I argue, attained through a subtle narrative strategy. In fact, the narrator locates the origins of medicine within a teleological framework, marked by strong emphasis on the heuristic method that characterizes the past, the present, and the future of medical knowledge at once.